2019
DOI: 10.3390/jcm8071003
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Value of Hyperuricemia on Renal Outcome after Contrast-Enhanced Computerized Tomography

Abstract: The aim of this study was to determine whether elevated serum level of uric acid (sUA) could predict renal outcome after contrast-enhanced computerized tomography (CCT). We used a historical cohort of 58,106 non-dialysis adult patients who received non-ionic iso-osmolar CCT from 1 June 2008 to 31 March 2015 to evaluate the association of sUA and renal outcome. The exclusion criteria were patients with pre-existing acute kidney injury (AKI), multiple exposure, non-standard volume of contrast, and missing data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
2
0
1
Order By: Relevance
“…One study found that hyperuricaemia was significantly associated with the risk of CI-AKI in patients with relatively normal serum creatinine after percutaneous coronary interventions in China (OR = 5.83) [11]. Similar findings demonstrated that UA ≥ 8.0 mg/dL was associated with an increased risk of CI-AKI in patients receiving contrast-enhanced computerized tomography (CCT) [12]. In experimental models, hyperuricaemia was associated with an absence of intrarenal crystals, the manifestation of tubular injury, macrophage infiltration, and increased expression of inflammatory mediators [13].…”
Section: Introductionmentioning
confidence: 83%
“…One study found that hyperuricaemia was significantly associated with the risk of CI-AKI in patients with relatively normal serum creatinine after percutaneous coronary interventions in China (OR = 5.83) [11]. Similar findings demonstrated that UA ≥ 8.0 mg/dL was associated with an increased risk of CI-AKI in patients receiving contrast-enhanced computerized tomography (CCT) [12]. In experimental models, hyperuricaemia was associated with an absence of intrarenal crystals, the manifestation of tubular injury, macrophage infiltration, and increased expression of inflammatory mediators [13].…”
Section: Introductionmentioning
confidence: 83%
“…A recent study from China proved that hyperuricemia was associated with CIAKI (OR = 2.363, 95% CI 1.653–3.377, P < 0.001) [ 40 ]. What’s more, it was also shown that patients with uric acid levels above 8.0 mg/dL not only had a greater risk of CIAKI but also an increased risk of hemodialysis [ 41 ]. Uric acid can promote oxidative stress and release a variety of proinflammatory factors, resulting in renal vasoconstriction and endothelial dysfunction [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…At present, some studies have found that high serum uric acid levels may be related to the occurrence of CI-AKI. A cohort study involving 1440 patients showed that serum uric acid levels ≥ 8.0 mg/dl were associated with an increased risk of CI-AKI [95].…”
Section: The 2018 Esurmentioning
confidence: 99%